2 `-5 `-Isomerically linked thrombin-binding aptamer (isoTBA) forms a stable unimolecular parallel G-quadruplex in the presence of Sr2+ Ions - Wagh, Atish A.; Fernandes, Moneesha (ChemistrySelect, 2019)
The ability of the isomeri 2 `-5 `-phosphodiester-linked thrombin-binding DNA aptamer pentadecamer G(2)T(2)G(2)TGTG(2)T(2)G(2) (isoTBA), to fold into G-quadruplex structures in the presence of different mono- and divalent cations is reported. Strikingly, Sr2+ ions cause isoTBA to fold into a stable parallel unimolecular G-quadruplex, in contrast to the antiparallel unimolecular G-quadruplex fold observed in the presence of K+. IsoTBA being advantageously more stable than TBA to nuclease degradation, may thus be useful in the selective detection of Sr2+ ions, which it can sense with a detection limit of similar to 55 mu M.
Keywords: 2 `-5 `-phosphodiester; parallel DNA G-quadruplex; strontium binding; thrombin-binding aptamer; unimolecular G-quadruplex

Implications of natural 3′-5′- linkages in the loop region of isomeric 2′-5′-linked thrombin-binding aptamer - Aher, Manisha; Kumar, Vaijayanti A.; Fernandes, Moneesha (Chemistryselect, 2024)
The backbone modification of the thrombin-binding aptamer (TBA) in the TT and TGT loop regions by isomeric 2 `-5 `-linkages was found to impose additive destabilizing effects on the thermal stability of the G-quadruplex structure. In contrast, the thermal stability of isomeric 2 `-5 `-linked TBA, i. e., isoTBA, was significantly improved by isomeric 3 `-5 `-phosphodiester linkages. The isoTBA, when modified with 3 `-5 `-linkages in both lateral TT loops (isoTBA202), exhibited higher thermal stability and enzymatic stability in comparison to other oligomers in the present study, and TBA202 showed higher antithrombin activity than other loop-modified TBA oligomers.
Keywords: 2 `-5 `-linked-linked DNA; DNA-isoDNA chimera; isoDNA; loop-modification; thrombin-binding aptamer